Pengaruh Bentuk Pakan Terhadap Laju Pertumbuhan Bobot Badan Ayam Broiler - Praptiwi, Irine Ike; Wahida, Wahida (AGRICOLA, 2023)
This study aims to determine the effect of mash feed form, pellets that use adhesives and without using adhesives on the growth rate of broiler chicken body weight. The treatment given in this study is the form of feed, A1: mash form, A2: pellet form without the addition of adhesive and A3: pellet using adhesive. The livestock used was 45 heads. The data were analyzed in a descriptive statistical manner. The results showed that the feed form affected the growth rate of broiler chicken body weight, with regression analysis obtained the equation Y = 364.38x + 192.88 with a correlation value (r) = 0.9882. The average growth rate of body weight in chickens given pelletized feed using adhesive (A3) has a higher value than the treatment of pelleted feed without adhesive and mash, with an average value of body weight growth rate of 387.56 g / head/week. It is necessary to pay attention to the particle size of feed ingredients to guarantee homogeneity. This will affect the nutrients as well as the digestibility of the feed made.